Prevalence and socio‐economic correlates of insomnia among older people in Anhui, China. (3rd September 2018) - Ma, Ying; Hu, Zhi; Qin, Xia; Chen, Ruoling; Zhou, Yanfei
Abstract : Objective: To measure the prevalence of insomnia and identify the socio‐economic correlates of insomnia among older people of Anhui Province of China. Methods: A cross‐sectional study was conducted among 3045 randomly selected consenting residents aged 60 and older from Anhui Province during 2013. Insomnia was assessed using the Athens Insomnia Scale (AIS). Data collected included: (i) demographics; (ii) socio‐economic status; (iii) social support; (iv) social contact; and (v) social capital. Results: Overall, 24% were found to have insomnia and 9% were found to have suspected insomnia according to the AIS score. After adjusting for potential confounders, participants having no fixed income, less social contact, less social capital and living alone were more likely to suffer from insomnia. Conclusions: A high prevalence of insomnia was found among older people in Anhui Province of China. Socio‐economic determinants should be addressed in devising policies aimed at improving sleep quality for older people in this region.